2023
DOI: 10.1177/02654075231179080
|View full text |Cite
|
Sign up to set email alerts
|

Actor and partner effects of prenatal coparenting behavior on postpartum depression in first-time parents

Abstract: Postpartum depression (PPD) is a common mental health complication of pregnancy and childbirth with long- and short-term consequences for the wellbeing and the functioning of parents. In particular, first-time parents seem to be at high risk for developing post-birth depressive symptoms as the transition to parenthood elevates stress and demands adjustment to significant changes. Prior research has mostly documented individual characteristics, such as prenatal depression and psychiatric history, as predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…This study drew on recent findings that revealed actor and partner effects of individual prenatal coparenting behaviors of first-time parents on postpartum depressive symptoms [ 13 ], and extended them by exploring associations between expectant parents’ dyadic interaction patterns before birth and depressive symptoms after birth. This goal was also driven by the understanding that, despite the central role of the emerging coparenting relationship in first-time parents’ daily adjustment and its development already beginning during pregnancy, the association between prenatal coparenting dynamics and postpartum depressive symptoms is extremely understudied.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study drew on recent findings that revealed actor and partner effects of individual prenatal coparenting behaviors of first-time parents on postpartum depressive symptoms [ 13 ], and extended them by exploring associations between expectant parents’ dyadic interaction patterns before birth and depressive symptoms after birth. This goal was also driven by the understanding that, despite the central role of the emerging coparenting relationship in first-time parents’ daily adjustment and its development already beginning during pregnancy, the association between prenatal coparenting dynamics and postpartum depressive symptoms is extremely understudied.…”
Section: Discussionmentioning
confidence: 99%
“…It included first-time heterosexual couples in the third trimester of pregnancy to 24 months post-birth. The inclusion criteria included (1) two-parent families expecting their first child and (2) singleton pregnancy, and the exclusion criteria included (1) significant pregnancy complications, (2) significant physical illness, especially cardiovascular diseases, (3) psychiatric disorders, and (4) the use of substantial medication or other substance (including heavy smoking) for full details and a description of the recruitment process, see [ 13 ]. The sample size was a priori determined by a power analysis using GPower* in order to reach 95% power to detect medium 0.15-sized effects.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations